SIMULATION ANALYSIS FOR ENERGY-ABSORPTION PROPERTIES OF A NESTED SQUARE THIN-WALLED TUBE - YU MingYang; MI CaiYing (Jixie qiangdu)
In order to improve the crashworthiness performance of the thin-walled metal tube,it presents a nested square thin-walled tube structure. The nonlinear explicit finite element method is used to study the energy-absorption characteristics of the nested square thin-walled tube. The results show that: during the collision happening in the axial direction,the deformation mode of the nested square thin-walled tube is asymptotic telescoping deformation; the specific energy absorption of the nested square thin-walled tube is 25. 72 kJ/kg,which is about 1. 64 times and 1. 31 times higher than the ordinary square tube and symmetrical four cells tube; reducing the thickness of the embedded walls can achieve the lightweight design target and shortening the height of the embedded walls and ribs can effectively reduce the initial peak crushing force. The nested structure can effectively improve the crashworthiness of thin-walled tubes. The research results provide a reference for the further research and engineering applications of vehicle energy-absorbing element.